2015
DOI: 10.1016/j.psychres.2015.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of corticosterone-induced BDNF alterations by the natural antioxidant alpha-lipoic acid alone and combined with desvenlafaxine: Emphasis on the neurotrophic hypothesis of depression

Abstract: Brain derived neurotrophic factor (BDNF) is linked to the pathophysiology of depression. We hypothesized that BDNF is one of the neurobiological pathways related to the augmentation effect of alpha-lipoic acid (ALA) when associated with antidepressants. Female mice were administered vehicle or CORT 20mg/kg during 14 days. From the 15th to 21st days the animals were divided in groups that were further administered: vehicle, desvenlafaxine (DVS) 10 or 20mg/kg, ALA 100 or 200mg/kg or the combinations of DVS10+ALA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 95 publications
1
13
0
3
Order By: Relevance
“…Circadian rhythm is modulated by corticosteroids secretion, which is regulated by the hypothalamuspituitary-adrenal gland axis (Llansola et al, 2013). It was observed in our study that repeated corticosterone treatment caused an elevation of serum corticosterone levels in mice, which was consistent with the previous studies (Sousa et al, 2015). This means that exogenous corticosterone results in an absolute increase in circulating serum corticosterone levels, an indicator of stress and depression in mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Circadian rhythm is modulated by corticosteroids secretion, which is regulated by the hypothalamuspituitary-adrenal gland axis (Llansola et al, 2013). It was observed in our study that repeated corticosterone treatment caused an elevation of serum corticosterone levels in mice, which was consistent with the previous studies (Sousa et al, 2015). This means that exogenous corticosterone results in an absolute increase in circulating serum corticosterone levels, an indicator of stress and depression in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Corticosterone (TCI, Japan) was dissolved in saline containing 0.1% dimethyl sulfoxide (DMSO) and 0.1% Tween-80. Corticosterone was injected subcutaneously once a day, between 09:00 and 11:30 a.m. (Sousa et al, 2015), at 40 mg/kg in a volume of 1 ml/kg as this dose reliably increases depression-like behavior in mice without altering the nonspecific motor activity (Fenton et al, 2015). Control mice received the same volume of saline.…”
Section: Drug Administration and Experimental Groupsmentioning
confidence: 99%
“…BDNF is one of the major downstream target genes of CREB, which is the most prevalent neurotropic factor in the cerebral dysfunction. BDNF is also acknowledged as one of the most extensively investigated target molecules controlling brain plasticity, survival, and differentiation in both periphery and central nervous system (CNS) [25]. Studies have shown that the non-polar extract of Gardenia Jasminoides has a rapid antidepressant activity, which mainly depends on the BDNF-TrkB signaling [9].…”
Section: Instructionmentioning
confidence: 99%
“…In a corticosterone-induced model of depression in mice, ALA showed antidepressant properties and reversed brain-derived neurotrophic factor reduction in the hippocampus and striatum ( de Sousa et al, 2015 ). In a d-amphetamine-induced model of mania, ALA was able to both prevent and reverse symptoms with comparable efficiency to lithium ( Macêdo et al, 2012 ).…”
Section: Mitochodrial Agentsmentioning
confidence: 99%